The Quality of Compost Made From a mixture of Oyster Mushroom Baglog Waste and Cow Manure with the Addition of Dekomposer of Promi, MA-11, and BPF - Muhammad Tirzady Prasetyo; I Gusti Made Kusnarta; Lolita Endang Susilowati; Mahrup (Jurnal Biologi Tropis, 2023)
:  This study aims to determine the quality of compost of a mixture of Oyster Mushroom Baglog waste and Cow Manure, using Promi (Promoting Microbes), MA-11 (Microba Alfaafa-11), and BPF (Phosphate Solubilizing Bacteria) decomposers. The experiment was arranged in a Completely Randomized Design (CRD), consisting of 4 ( Four) treatments: P0 = Baglog Oyster Mushrooms and Manure with a ratio = 1:2 without decomposers, P1 = Baglog Oyster Mushrooms and Manure with a ratio = 1:2 plus Promi, P2 =Baglog Oyster Mushrooms and manure with a ratio = 1:2 plus MA 11, P3=Baglog Oyster Mushrooms and Manure with a ratio of = 1:2 plus (BPF). Each treatment was repeated three times to obtain 12 experimental units. Parameters measured were: texture, pH, C-organic, N-total, C/N Ratio, Temperature (Temperature), Compost Color, and Compost Odor. The results showed that of the three decomposers used in this study, Promi was better at decomposing compose for two months. Promi is faster in changing the color of the compost to black, faster in reducing the temperature of the compost, has a pH of 6.81, and has the lowest organic C content and total N content of 0.94%. Of the three decomposers used in this study, Promi is better and faster for producing compost from a mixture of baglog and cow manure than the other treatments.